The Global Distribution of Trademarks: Some Stylized Facts - Baroncelli, Eugenia (World Bank, Washington, D.C., 2013)
Trademarks are words, signs, symbols, or combinations thereof that identify goods as manufactured by a particular person or a company, therefore allowing consumers to distinguish between goods originating in different sources. Trademarks belong to the wider family of intellectual property rights (IPRs), and once registered benefit from legal protection against unauthorized use by entities other than the legal owner. While some suggest that cross-border registrations of IPRs may be associated with welfare transfers from developing to industrial countries, surprisingly little is known about an important component of the global IPR system, namely, the worldwide distribution of trademark registrations. This study provides the first step in filling this gap in the literature. Its purpose is to present some new stylized facts which emerge from the analysis of a dataset compiled by the authors based on the statistical information published by the World Intellectual Property Organization (WIPO). Questions of interest include the distribution of trademarks between countries of different income levels, the share of trademark registrations accounted for by foreign residents and its variation across different income groups, the extent to which poor countries participate in the international trademark system, and the distribution of registrations across different sectors of the economy.